EXPERIMENTAL DETERMINATION OF THE STABILITY CONSTANTS OF NASO4- AND NAB (OH)40 IN HYDROTHERMAL SOLUTIONS USING A NEW HIGH-TEMPERATURE SODIUM-SELECTIVE GLASS ELECTRODE - IMPLICATIONS FOR BORON ISOTOPIC FRACTIONATION - Pokrovski G.S.; Schott J.; Sergeyev A.S. (My University, 1995)
A new sodium-selective glass electrode was used to measure the association constants of the sodium-sulfate (NaSO4−) and sodium-borate (NaB(OH)40) ion pairs at temperatures from 50° to 200°C. These data were used to generate, within the framework of the revised HKF model, NaSO4− and NaB(OH)40 equation of state parameters. Calculation of NaB(OH)40 association constants at temperatures up to 500°C and pressures up to 5 kbar demonstrates that this ion pair dominates boron speciation in sodium-rich hydrothermal fluids at pH ≥ 8. Because it has been shown that boron isotopic fractionation in natural processes is strongly affected by its aqueous speciation, the formation of NaB(OH)40 complexes cannot be neglected when using boron isotopes to estimate water-rock interactions occurring in the continental and oceanic crust at moderate and high temperatures.